Arte Pará: etnografia e interpretação em um salão de artes visuais na Amazônia - FLETCHER, John (Universidade Federal do Pará, 2019)
The presente paper brings ethnographic reports on experiences with artists, curators, organizers and technicians in the assembly of the Arte Pará exhibit, between the years of 2012 to 2015, held in the city of Belém. An integral part of a doctoral research, this clipping is based on synchronic and dialogical methodological premises from authors, such as Vincent Crapanzano and James Clifford, problematized by contributions of thoughts by Walter Mignolo, Eva Marxen, Beatriz Sarlo, Homi Bhabha and Johannes Fabian, among others. Thus, in order to expose a more critical view of our asymmetric present, this research aims at conferring other interpretative dimensions to the general dynamics of human experience.